Chemical Composition and Antioxidant Activity of Aquilaria Malaccensis Leaf Extract - Nik Noor Asma, Nik Wil; Saiful Nizam, Tajuddin; Nor Adila, Mhd Omar (2014)
In this study, water extraction (WE) and methanol etraction (ME) of A.malaccensis dried leaves (DL) and fresh leaves (FL) were investigated for its in vitro antioxidant activity that may contribute to their pharmacological effects. Total phenolic content (TPC) of this plants were determined by Folin-Ciaocalteu assay while antioxidant potential were evaluated by CUPRAC and DPPH method.